MEWUJUDKAN NEGARA HUKUM DEMOKRATIS KONSTITUSIONAL BERDASARKAN PANCASILA DAN UNDANG-UNDANG DASAR 1945 - Damrah Mamang (VERITAS, 2016)
The commitment, step, and efforts to realize the vision of Indonesia as ademocratic constitutional state law based on Pancasila and the 1945 Constitutionis a necessity and the duty of every constitutional state officials as well as citizensand even the whole nation, regardless of political and social strata bears. In theperspective of philosophical, sociological, and juridical, can be formulated in adynamic perception that in a democratic constitutional state, a profile of thecountry remains the ideal state at once realistic that can be manifested. In thecontext of Indonesia, for example, a living reality, Indonesia as a unitary staterepublic Indonesia is a country of law (the rule of law) must always be built andlived in a discursive procedure. For the law to be created and applied in a manneryng properly, fairly and impartially, that's the ideal law namely that the law is builton and the value of ethics and high morality of a nation. In the perspective ofphilosophy of law ideal of a state of law is Bonum Commune, namely the creationof a political sisial system that guarantees the fulfillment of the basic needs of allcitizens fairly. This is the mandate of the sacral fundamental in the history of therepublic of Indonesia reached the age of 71 years of independence from the fiveprecepts of Pancasila, seliruh social justice for the people of Indonesia,